Acute effect of static and dynamic stretching on tone and elasticity of hamstring muscle and on vertical jump performance in track-and-field athletes - Meerits, T.; Bacchieri, S.; Pääsuke, M.; Ereline, J.; Cicchella, A.; Gapeyeva, H. (Acta Kinesiologiae Universitatis Tartuensis, 2014)
The aim of the study was to evaluate and compare acute effect of static and dynamic stretching exercise on hamstring muscles tone and jump performance in trained track-and-field athletes. Twelve male track-and-field elite athletes (mean age: 22.0±2.1 years) who trained speed and explosive power (sprint, jumps and decathlon) voluntarily joined in the study. Muscle tone and elasticity characteristics (frequency and logarithmic decrement, respectively) of hamstring muscles (biceps femoris and semitendinosus) were measured by Myoton PROdevice (Myoton Ltd, Estonia). Squat jump height was measured by telemetric system BTS G-studio (BTS S.p.A., Italy). All characteristics were measured before and after stretching exercise. Frequency of hamstring muscles did not differ significantly after static and dynamic stretching. Hamstring muscle`s decrement decreased by 2.9% (p<0.01) after static stretching. Jump height increase by 7.1% (p<0.01) after dynamic stretching and decrease by 5.2% (p<0.05) after static stretching was noted. Muscle tone and elasticity characteristics did not correlate with jump height. This study shows that dynamic stretching has a positive effect on explosive power in trained track-and-field athletes and it is preferable to use static stretching after warm-up of these athletes.